2019
DOI: 10.3390/nano9081068
|View full text |Cite
|
Sign up to set email alerts
|

Endohedral Fullerene Fe@C28 Adsorbed on Au(111) Surface as a High-Efficiency Spin Filter: A Theoretical Study

Abstract: We present a theoretical study on the adsorption and spin transport properties of magnetic Fe@C28 using Ab initio calculations based on spin density functional theory and non-equilibrium Green’s function techniques. Fe@C28 tends to adsorb on the bridge sites in the manner of C–C bonds, and the spin-resolved transmission spectra of Fe@C28 molecular junctions exhibit robust transport spin polarization (TSP). Under small bias voltage, the transport properties of Fe@C28 are mainly determined by the spin-down chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…This amount of SFE has been obtained in other work including 23 . Though these SP values in the Fermi energy make molecules promising structure in spintronics, this value is low in comparison with the spin-filters obtained in other works 21,22,59 . On the other hand, it is possible to achieve a higher SFE by increasing the length of the molecule.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…This amount of SFE has been obtained in other work including 23 . Though these SP values in the Fermi energy make molecules promising structure in spintronics, this value is low in comparison with the spin-filters obtained in other works 21,22,59 . On the other hand, it is possible to achieve a higher SFE by increasing the length of the molecule.…”
Section: Resultsmentioning
confidence: 54%
“…Also they had calculated the spin polarization (SP) as a function of gate voltage. A theoretical study on the adsorption and the spin transport properties of Fe@C 28 was reported by Xu et al 21 using spin DFT and NEGF techniques. Caliskan had investigated the SP of partial density of states (PDOS) and current–voltage characteristics of N@C 20 22 and X@C 70 (X = B, N) 23 attached to Au electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…the gold substrate. For the initial guess distances between the fullerenes and the gold substrate we refer to the work reported in [24]. The first configurations we relax, that we call "geometries A", are reported in Fig.…”
Section: Methodology and Computational Detailsmentioning
confidence: 99%
“…Фуллерены C n с n < 60 относятся к так называемому классу малых фуллеренов. В настоящее время большое число исследований посвящено изучению свойств малых фуллеренов: С 20 [2,3], С 24 [4,5], С 28 [6,7], С 36 [8,9]. Одним из малых фуллеренов является фуллерен С 26 , существование которого экспериментально было подтверждено в ряде работ [10,11].…”
Section: Introductionunclassified